Maliseet Cultivation and Climatic Resilience on the Wəlastəkw/St. John River During the Little Ice Age - Hall, Jason (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
This article examines how Maliseets extended maize cultivation in the Americas northeastward to the Wəlastəkw (St. John River) using Indigenous cultivation techniques and knowledge of riverine microclimates during the Little Ice Age, a time when many peoples in the Northern Hemisphere abandoned cultivation. It also suggests that agriculture in New Brunswick began as an Indigenous complex, and that the cultivation work of Indigenous people prepared some of the field and town sites later used by Acadian and British colonial farmers.